Physiology of sport and exercise / W. Larry Kenney, Jack H. Wilmore, David L. Costill. - Kenney, W. Larry; Wilmore, Jack H., 1938-2014; Costill, David L. (Human Kinetics, 2024)
Details human physiological responses to exercise and sport. With digital aids, including animations and video, the text clearly illustrates how the body performs and responds to physical activity.